Covid-19 and seaborne trade: The Italian perspective. (June 2022) - Ferrari, Claudio; Persico, Luca; Tei, Alessio
Abstract: Covid-19 pandemic impacted on all major trade flows, shuffling global value chains and pushing major industries to re-think their procurement strategies. While long term impacts are still subject to speculation, the immediate response of local industries need to be evaluated in order to target relevant policy interventions and to understand which economic players have been hit the most. Current paper tries to fill such gap, using the Italian Custom Agency database for verifying which trade sectors and ports suffered the most from the Covid-19 first wave. In order to achieve the research goal, all containerized import and export flows have been collected for the period 2012–2020, comparing historical patterns with the one observed in the first semester 2020. Results aim at contributing to the current understanding of the crisis' impact and they will be used for driving future recovery plans.